The concept of Kingship of Themistius and Ammianus Marcellinus: The case of the emperor Valentinian I (De Rebus Antiquis, 2020)
In the context of Late Antiquity, we observe the ideals of Royalty of two authors who shared the political events between the governments of Constantius II to Theodosius (337-395 AD), namely: the philosopher Themistius (317-388 AD) with his political speeches; and the military Ammianus Marcellinus (325 / 330-395 AD) with his work Res Gestae. During our study, we will seek to observe the characteristics of each author, and converge their life experiences to meet the convergent and divergent points of its concepts around the Imperial responsibilities. In the meantime, we emphasize the interactions between Romans and barbarians, very noticeable at that time; and how this process of interaction of cultures has influenced the thinking of the late-ancient writers studied here. Observing how a philosopher and a military developed such ideals in relation to the ruler: Valentinian I (364-375 AD), for that we made a more specific analysis of VI Speech of Themistius - the Brotherly Love or About humanity - and the XVI - XXX Books of Ammianus Marcellinus. Thus, in a time of great cultural socio-political effervescence, two non-Christian writers have written their work, in order to re-member your audience the importance of the virtues and both based on examples from the classical tradition.
Keywords: Late Antiquity; Royalty; Themistius; Ammianus Marcellinus